2008
DOI: 10.1149/1.2969418
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytically Generated Pt∕C–TiO[sub 2] Electrocatalysts with Enhanced Catalyst Dispersion for Improved Membrane Durability in Polymer Electrolyte Fuel Cells

Abstract: Platinum/carbon/titanium oxide ͑Pt/C-TiO 2 ͒ electrocatalysts were prepared by a heterogeneous photocatalysis method wherein the semiconductor optoelectronic properties of TiO 2 were exploited to facilitate photoreduction of a platinum precursor on the surface of the composite whole yielding excellent platinum dispersion. The TiO 2 loading in the electrocatalyst was varied in the ranges: 5-10 wt % and the Pt content was varied from 5 to 50 wt %. The physical and electrochemical characteristics of these new-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…2 Briefly, commercially available carbon blacks and TiO 2 (Degussa P-25) were mixed in a pre-selected wt% ratio and dispersed in 50 mL of deionized water (Corning Megapure) with the aid of an ultrasonic bath. The dispersion was then transferred to a 500 mL volumetric flask where 13⋅5 mL HCOOH (96%) and the required amount of platinum salt precursor (K 2 PtCl 6 , Pt 40⋅11%, Alfa Aesar) to generate different Pt wt%, ranging from 5 to 50, were added and then the total volume was adjusted to 500 mL.…”
Section: Preparation Of Pt/c-tio 2 Nanocompositementioning
confidence: 99%
See 2 more Smart Citations
“…2 Briefly, commercially available carbon blacks and TiO 2 (Degussa P-25) were mixed in a pre-selected wt% ratio and dispersed in 50 mL of deionized water (Corning Megapure) with the aid of an ultrasonic bath. The dispersion was then transferred to a 500 mL volumetric flask where 13⋅5 mL HCOOH (96%) and the required amount of platinum salt precursor (K 2 PtCl 6 , Pt 40⋅11%, Alfa Aesar) to generate different Pt wt%, ranging from 5 to 50, were added and then the total volume was adjusted to 500 mL.…”
Section: Preparation Of Pt/c-tio 2 Nanocompositementioning
confidence: 99%
“…In all the cases, further analyses of these RDE data revealed electron stoichiometry values close to 4 signalling that the ORR on the Pt/C-TiO 2 surface was by-passing the free radical generating 2e -intermediate step. 2 This finding has positive implications for the PEM stability in the MEA as electrochemically generated hydrogen peroxide is one of the sources of free radical species responsible for PEM degradation in an operating fuel cell (see above). carbon first undergoes corrosion as signalled by the rapid positive excursion of the electrode potential.…”
Section: Oxygen Reduction Reaction (Orr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modification of carbon nanotubes [1][2][3] or nanostructured carbon [4][5][6][7][8][9][10][11][12] has been undertaken. Another strategy to stabilize the support is to develop metal-oxide substrates as reported for SiO 2 [13], NbO 2 [14], MnO x [15], WO x [16,17], SnO 2 [18] and TiO x [15,[19][20][21][22][23][24][25][26][27][28]. Pt deposited on such substrates shows an increase of the activity for the oxygen reduction reaction (ORR) as compared to Pt/C.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-TiO 2 /C shows improved stability in polymer electrolyte membrane fuel cells (PEMFCs) compared with Pt/C [22].In spite of the amount of titanium dioxide and the crystalline phase (TiO 2 anatase/rutile phase) it was found that, it modifies the strength of the interaction between the substrate and the metal nanoparticles [23,24]. The good effect of addition TiO 2 may be attributed to two factors which are: the changes in the Pt-d electronic properties and the geometric effect that leads to the Pt-Pt bonding distance contraction and hence results in a sensible improvement of the electrochemical reactions [25,26].Titanium oxidebased cathode, synthesized from oxy-titanium tetra-pyrazinoporphyrazine by the oxidation under a low partial pressure of oxygen using carbon nanotubes as a support, showed high reactivity in the four-electron reduction of oxygen [27].…”
Section: Introductionmentioning
confidence: 99%